Efeito da ovariectomia e treinamento de força no conteúdo lipídico no músculo esquelético, fígado, coração, depósitos de gordura e perfil lipídico - Leite, Richard Diego (Universidade Federal de São Carlos, 2010)
The aim of the present study was to investigate the effects of resistance training on skeletal muscle lipid content, liver lipid content, heart lipid content, fat depots and lipid profile in ovariectomized rats. Wistar adult female rats were grouped into: sedentary (Sed-intact); ovariectomized sedentary (Sed-Ovx); strength trained (ChronicEx-intact) and ovariectomized strength trained (ChronicEx-Ovx) (n= 10 per group). A 12-week strength training period that consisted in climbing a 1.1-m vertical ladder with weights attached to rats tail was used. The sessions were performed once every 3 days with 4-9 climbs and 8-12 dynamic movements per climb. Ovariectomy increased liver lipid content, fat depots, heart and muscle lipid content. There was an increase in atherogenic index and negative change in lipid profile due to ovariectomy. Resistance training decreased lipid content in liver, soleus, tibialis anterior, fat depots (mesenteric and retroperitoneal) and lipid profile, independently of ovarian hormone status. These results indicate the potential benefits of resistance training as an alternative strategy to control the effects of ovariectomy on fat depot, lipid profile, and tissue lipid content.
Keywords: Metabolismo; Exercício resistido; Bioenergética; Menopausa; Ovariectomia; Treinamento resistido; Conteúdo tecidual de lipídio; Depósitos de gordura; perfil lipídico; Resistance training; Ovariectomy; Tissues lipid content; Fat depots; Lipid profile; CIENCIAS BIOLOGICAS::FISIOLOGIA